O cinema popular e dialético de Tomás Gutiérrez Alea - Leonardo Ayres Furtado (2007)
This study intends to examine and discuss critically the work of the Cuban Tomas Gutierrez Alea, with the main point to reflect on the social function of cinema. The concept of "Popular Cinema", presented by filmmaker, highlight the role of cinema as entertainment and artistic spectacle, but also defines as one way to promote ideas in viewers and actions that modify the reality.